Affixation to The Short Story Mengapa Mereka Berdoa Kepada Pohon By Faisal Oddang - Fatmasari, Ika; Guniarti, Dian; Pratami, Fisnia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to discuss the affixation process in the short story entitled Mengapa Mereka Berdoa kepada Pohon by Faisal Oddang. In this research, the type of research used is descriptive qualitative. Qualitative descriptive research was used to analyze this novel. The aim of this research is to analyze the form of attachment in the short story Mengapa Mereka Berdoa kepada Pohon by Faisal Oddang. Material collection was carried out using listening techniques, after which it was continued with note-taking techniques, namely recording the information needed for research recorded from the results of listening. Based on the results of data collection, affixation forms were obtained which were divided into four, namely prefixes with 45 data, infixes with 6 data, suffixes with 17 data, and confixes with 4 data. The most common form of affixing is prefix. This affixation process can enrich knowledge about language and create a rich reading experience for readers. It is hoped that this research will provide further understanding of the use of Indonesian in a literary context, as well as being useful in providing knowledge, especially in the field of morphological studies.